Effects of Social and Organizational Support on the Satisfaction of International Students and Career Commitment - Hahm, Sang-Woo (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Perceived organizational support and perceived social support affect individual performance. Their influence may or may not be the same depending on the situation. This study describes the different effects of perceived organizational support and perceived social support on organizational satisfaction and social life satisfaction. Furthermore, it proves that perceived organizational support and perceived social support enhance the organizational (school) satisfaction and social life (life of studying abroad) satisfaction of international students. On addition, through this process, they also increase the career commitment of students. This paper identifies the importance of perceived organizational support and perceived social support necessary to improve the international students' performance, and explain the impact and relevance of their different satisfactions. Through this, this article proposes ways to improve the performance of international students and the discriminatory relevance of perceptions of different objects.